The Appraisal of the Teacher’s Talk to Enhance Students’ Critical Thinking Skills Through Narrative Text in Design Thinking Pedagogy - Inggy Yuliani Pribady (Universitas Dian Nuswantoro, 2018)
Design thinking has become a new trend at schools in different countries. There are many educators who are eager to adopt Design thinking as an effective strategy for helping their students to learn through solving real-world problems. For Indonesian context, Design Thinking provides a new innovative ground of teaching English in EFL setting. Teachers engage the students in collaborative problem solving, creative challenge, and foster social –emotional balance and stability. The paper portrays how the teacher conducts learning activities in the Empathy stage of Design Thinking to build students’ critical literacy from the start. The attitude domain of the appraisal theory is used to disclose the way of the teacher to guide the students to express their emotional reaction toward the story, to assess the behavior of the characters and construe the value of things in the text.The classroom discourse analysis shows that the teacher’s talk by employing the attitude resources plays important role in supporting the students to develop their critical thinking capacity and build their narrative’s content knowledge.The result of the study is expected to enrich the reference of appraisal discourse analysis theory and provide the example of the teaching practice for enhancing students’ critical thinking capacity in Narrative learning through Design Thinking pedagogy.